Tuning Functional Amyloid Formation Through Disulfide Engineering - Balistreri, Anthony; Kahana, Ethan; Janakiraman, Soorya; Chapman, Matthew R. (Frontiers in Microbiology, 2020)
Many organisms produce ‘functional’ amyloid fibers, which are stable protein polymers that serve many roles in cellular biology. E. coli and other Enterobacteriaceae assemble functional amyloid fibers called curli that are the main protein component of the biofilm extracellular matrix. CsgA is the major protein subunit of curli and will rapidly adopt the polymeric amyloid conformation in vitro. The rapid and irreversible nature of CsgA amyloid formation makes it challenging to study in vitro. Here, we engineered CsgA so that amyloid formation could be tuned to the redox state of the protein. A double cysteine variant of CsgA called CsgACC was created and characterized for its ability to form amyloid. When kept under oxidizing conditions, CsgACC did not adopt a β-sheet rich structure or form detectable amyloid-like aggregates. Oxidized CsgACC remained in a soluble, non-amyloid state for at least 90 days. The addition of reducing agents to CsgACC resulted in amyloid formation within hours. The amyloid fibers formed by CsgACC were indistinguishable from the fibers made by CsgA WT. When measured by thioflavin T fluorescence the amyloid formation by CsgACC in the reduced form displayed the same lag, fast, and plateau phases as CsgA WT. Amyloid formation by CsgACC could be halted by the addition of oxidizing agents. Therefore, CsgACC serves as a proof-of-concept for capitalizing on the convertible nature of disulfide bonds to control the aggregation of amyloidogenic proteins.